Analisis Implementasi SOP Kesekretariatan dan Kepaniteraan dalam Mewujudkan Akuntabilitas Publik di Pengadilan Negeri Sukoharjo - Azahra Aulia Damayanti; Dristya Herra Talitha; Olivia Intan Widi Prabawani; Allycia Vania Sherly; Amrihakim Dwi Faunnas; Dhanifa Whisnu Anandha; Surya Putra Ardana; Yokhebed Arumdika (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) in the secretariat and clerkship divisions in realizing public accountability at the Sukoharjo District Court and to identify the obstacles faced in its implementation. This research employed an empirical legal research method with a qualitative descriptive approach. Data were obtained through observation, interviews, and literature studies on laws and regulations, references, and documents related to judicial administrative services. The results indicate that the implementation of SOPs in the secretariat and clerkship divisions has been carried out quite effectively through the application of One-Stop Integrated Services (PTSP), electronic-based administrative services, and structured division of work responsibilities. The implementation of these SOPs supports the creation of administrative services that are more transparent, orderly, and accountable. However, several obstacles remain, including limited human resources, disruptions in information technology systems, high administrative service workloads, and the limited public understanding of digital court services. Therefore, improving the quality of human resources, optimizing information technology facilities, and strengthening public service socialization are necessary to support the effectiveness of SOP implementation and improve the quality of public services within the judicial environment.